High school agriculture teachers' intentions to continue teaching - Ismail, Normala; Miller, Greg (Horizon Research Publishing, 2020)
A descriptive survey study was used to examine factors that influence high school agriculture teachers’ intentions to continue teaching in Iowa. The online questionnaire was administered to 252 agriculture teachers, and 119 teachers completed the survey. A four-point Likert-type scale was used to measure agriculture teachers’ intentions to continue teaching. The overall mean and standard deviation is 2.64 (.64) for the eight influential factors, which indicates that these factors slightly influenced teacher intentions to continue teaching. The multinomial logistic regression model using the stepwise forward method was used to predict the likelihood of individuals’ plans to continue teaching. The model was statistically significant (χ2 = 39.97; p = 0.01), and the following significant, influential factors can explain 31 percent (Pseudo R2=.31) of the variance: teacher recognition (p=.001), teaching as a right career (p=.035), family expectation of staying (p=.035) and teaching makes oneself feel good (p=.040). Findings from this study support evidence from previous research that reported teachers with strong self-esteem and belief that teaching is the right career for them and will remain longer in the profession.